Capillary hemangioma in the ileum: Obscure small-bowel bleeding in an elderly person - Wang, Bangting; Luo, Zhongguang; Zheng, Wanwei; Zhang, Jun; Liu, Jie (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Wang B, Lou Z, Zheng W, Zhang J, Liu J. Capillary hemangioma in the ileum: Obscure small-bowel bleeding in an elderly person. Turk J Gastroenterol 2018; 29: 520-1.